2021
DOI: 10.1080/09540121.2021.1981816
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-care viral load testing among adolescents and young adults living with HIV in Haiti: a randomized control trial

Abstract: HIV viral load (VL) monitoring can reinforce antiretroviral therapy (ART) adherence. Standard VL testing requires high laboratory capacity and coordination between clinic and laboratory which can delay results. A randomized trial comparing point-of-care (POC) VL testing to standard VL testing among 150 adolescents and young adults, ages 10-24 years, living with HIV in Haiti determined if POC VL testing could return faster results and improve ART adherence and viral suppression. Participants received a POC VL t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
2
0
1
Order By: Relevance
“… 21 In this study, all participants were on first-line efavirenz-based regimens, there were few participants with viral failure (16 of 390, 4.1%), and the research team conducted clinical management in the intervention arm, meaning it is difficult to determine the contribution of point-of-care testing within the overall implementation strategy. Trials among children in Kenya, 17 adolescents in Haiti, 18 and adults in Nigeria 19 , 20 found that point-of-care VL testing improved time to receipt of VL results by 2, 4, and 20 weeks, respectively, with improved switching to second-line ART. However, none of these trials found a clear impact on viral suppression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 21 In this study, all participants were on first-line efavirenz-based regimens, there were few participants with viral failure (16 of 390, 4.1%), and the research team conducted clinical management in the intervention arm, meaning it is difficult to determine the contribution of point-of-care testing within the overall implementation strategy. Trials among children in Kenya, 17 adolescents in Haiti, 18 and adults in Nigeria 19 , 20 found that point-of-care VL testing improved time to receipt of VL results by 2, 4, and 20 weeks, respectively, with improved switching to second-line ART. However, none of these trials found a clear impact on viral suppression.…”
Section: Discussionmentioning
confidence: 99%
“…To date, 2 point-of-care assays have been approved as accurate by the WHO for use in LMICs 13,14 and have been evaluated in our setting. 15,16 Clinical trials of these assays among children, 17 adolescents, 18 and adults [19][20][21] have demonstrated shorter turnaround times, but effects on clinical outcomes have been mixed.…”
Section: Introductionmentioning
confidence: 99%
“…La mayor demanda de pruebas de CV-VIH ha contribuido a la demora en los resultados, afectando las terapias de recuperación y su adherencia (Gous et al, 2018). Este problema crea la necesidad de plataformas dinámicas para atender la demanda de la población con resultados oportunos, como es el caso del equipo del GeneXpert (Reif et al, 2021;Zamboni Berra et al, 2021). La incorporación de nuevos sistemas reduciría el tiempo de respuesta, los procesos y el costo; aumentando la eficacia y eficiencia del laboratorio (Curioso, 2020).…”
Section: Introductionunclassified